PRODUCT CONFIGURATION CAPABILITY FOR IMPROVING MARKETING PERFORMANCE OF SMALL AND MEDIUM METAL INDUSTRY IN CENTRAL JAVA - INDONESIA - Ahmad Hanfan (Jurnal Manajemen dan Kewirausahaan, 2021)
This study explored and examined the role of product configuration capabilities to improve marketing performance. Product configuration capability represented the company's capability to configure products with visibility/clarity of product origin, products that were different from competitors and products that were difficult to imitate. This capability indicated that the products produced by the company were more efficient and quality than that of others. The results found that product configuration capabilities could improve product success, growth in product marketing reach and market share product. This study was expected to provided a contribution to both theoretical and practical knowledge of strategic management. Business players had focussed on developing dynamic capabilities to address the constantly changing business environment.